HUBUNGAN PENGETAHUAN DAN PERILAKU IBU TENTANG KEJADIAN ANEMIA DALAM KEHAMILAN DI WILAYAH UPTD PUSKESMAS LAMPAHAN KECAMATAN TIMANG GAJAH KABUPATEN BENER MERIAH - Indah Dayana; Nova Arami; Rahmayani; Nurlaely HS (Akper Kesdam I/Bukit Barisan Padang, 2026)
ABSTRACT Anemia in pregnancy is a condition where a pregnant woman experiences a deficiency of iron in her blood. Anemia or often called anemia is a condition where the red blood is less than normal, which is usually called the Hemoglobin (Hb) level. This research uses quantitative methods with a cross sectional approach, the population in this study is pregnant women with anemia at the Lampahan Community Health Center. The sample in this study was simple random sampling. This sampling can be done randomly, so the sample used in this study was 60 respondents/ pregnant women. The analysis in this study used chi-square analysis. The research results showed that the factors related to Anemia in Pregnancy were the Knowledge factor (p-value=0.028), Maternal Age (p-value=0.015), Behavior (p-value=0.022), Parity (p-value=0.025), Occupation (p-value=0.030), KEK Status (p-value=0.007), Education (p-value=0.032)Status Economics(p-value=0.018). It is hoped that this research can serve as input for pregnant women in preventing anemia in pregnancy by recommending consuming Fe tablets, changing healthy eating patterns, following family planning, and having additional work. Keywords : Knowledge, Behavior, and Anemia in Pregnancy